2020
DOI: 10.1111/jch.13974
|View full text |Cite
|
Sign up to set email alerts
|

Frequency & factors associated with apparent resistant hypertension among Ghanaians in a multicenter study

Abstract: assumes financial management of the study as a fiduciary agent and primary contractor for the Funders. Consistent with antitrust laws that govern industry interactions, each Participant Company independently and voluntarily will continue to develop its own marketing and pricing strategies reflecting, among other factors, the Company's product portfolios and the patients it serves. For the avoidance of doubt, the Participant Companies committed not to: (a) discuss any price or marketing strategy that may involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Non-adherence, both with AHDs and life style changes, play a role and are discussed, as are the reasons for the non –compliance. A recent study from Morocco [ 87 ], with 73% UBP in hypertensives found that therapeutic inertia (TI) (adjusted odds ratio AOR 18.2) AHD non-adherence, obesity/overweight, low income, HT family history, and male sex all contributed [ 87 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Non-adherence, both with AHDs and life style changes, play a role and are discussed, as are the reasons for the non –compliance. A recent study from Morocco [ 87 ], with 73% UBP in hypertensives found that therapeutic inertia (TI) (adjusted odds ratio AOR 18.2) AHD non-adherence, obesity/overweight, low income, HT family history, and male sex all contributed [ 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure controlled in 32.9% Factors causing and contributing to non –adherence with medications and life style modifications and BP control Multiple daily drug doses Patient- health provider relationships Co- morbidities (compelling indications) Long duration of treatment Cost of Medications Adverse drug Forgetfulness and cigarette smoking Older age (>.65 years old) Physical inactivity Adding Salt to diet Chat chewing Coffee consumption Low socio-econpmic status Antihypertensive monotherapy Fake or Substandard Antihypertensive medications Poor quality amlodipine (29%) and captopril (26%) in generic versions or produced from certain global zones had <85% of the active pharmacological ingredient True Resistant/Refractory Hypertension Patient resistant to 5 antihypertensive drug combination including a diuretic and a mineralocorticoid antagonist (MRA) such as spironolactone. References [ [88] , [89] , [90] , [91] , [92] , [93] , [87] , [94] , [95] ]: UBP – Uncontrolled Blood Pressure. References [ [88] , [89] , [90] , [91] , [92] , [93] , [87] , [94] , [95] ]: …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations